Mahasiswa Kukerta Unri dan BPJPH Sosialisasi Sertifikat Produk Halal di Desa Mekarsari - Enda Puspita Sari; Amesza Ghadijah; Asiatunnur Asiatunnur; Azmi Kurniawansah; Desy Maya Sari; Dhita Arisandy Thalia Resqi; Mely Nofriani; Pedri Ilham; Randa Eka Syahputra; Vera Riyani; Widya Firdia Sari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The Mekarsari Village KKN student activity program with a qualitative descriptive method was carried out in Mekarsari Village, Lirik District, Indragiri Hulu Regency, to be precise at the Meranti Jaya Sports Hall (GOR). Indonesia's population with a Muslim majority makes the need for halal products very large. There needs to be a guarantee of halal products for incoming and outgoing products circulating in Indonesia. The halalness of a product can be determined by carrying out a halal certification by conducting product inspections starting from the selection of raw materials, the production process, to final product results. On this basis, it is necessary to certify halal products for UMKM owners. This of course will improve the UMKM economy of the population. Therefore, suggestions for the future are that residents are expected to participate in halal logo verification activities so that UMKM owners can understand the importance of halal logo certification for their businesses. From the activities carried out in Mekarsari Village, it can be concluded that the importance of halal logo certification for UMKM owners in Mekarsari Village has an effect on the economic progress of the residents of Mekarsari Village.